Caregiver Strengths, Attitudes, and Concerns About Reading and Child Development in the Dominican Republic. (July 2020) - Mathieu, Irène; Wallis, Kate; Japa, Ingrid; Cordero, Ramona; Deverlis, Adriana; Steenhoff, Andrew P.; Lowenthal, Elizabeth
Background . Parents' beliefs about and engagement in reading aloud to young children and other positive parenting practices have been associated with early childhood development (ECD) and later achievement. Aim . This exploratory study sought to assess parental attitudes and self-reported practices regarding ECD in a rural, low-income community in the Dominican Republic with many risk factors for ECD delays, including high rates of poverty, iron-deficiency anemia, and malnutrition. Methods . We used the Parent Reading Belief Inventory and open-ended questions to evaluate parental beliefs regarding reading, self-efficacy in promoting child development, current positive parenting practices, and parents' concerns about the development of their 0- to 5-year-old children in Consuelo, Dominican Republic. We explored associations between demographic factors and strength of positive parenting beliefs and practices. Results . Overall participants had positive attitudes toward reading and their own importance in promoting their children's development. Participants with at least some high school education had significantly higher Parent Reading Belief Inventory scores ( P = .03) than those with less formal education. Participants reported frequently singing, talking, and playing with their children, but less frequently reading with them. Few participants had access to reading materials for young children. Parental interest in programs to support ECD was high. Parents raised concerns about their children's behavior, personal and educational attainment, and early literacy. Conclusion . Children whose parents have less formal education may benefit most from interventions to promote beliefs and practices likely to improve ECD. In this community, there is high interest in learning more about ECD.